Inhibition of GTPase Rac1 expression by vitamin D mitigates pressure overload-induced cardiac hypertrophy - Ali Moradi (Elsevier, 2021)
Background: 1, 25-dihydroxy Vitamin D3 (VitD) attenuates left ventricular hypertrophy (LVH), but the mechanisms remain to be portrayed in-depth. The small GTPase Rac1 plays a pivotal role in cardiovascular pathology, especially LVH. Here, we tested whether VitD exerts its anti-LVH effects by counteracting the small GTPase Rac1 expression. Methods: In Wistar rats, pressure overload-induced LVH was created by abdominal aortic banding. The animals were intraperitoneally administered VitD (0.1 µg/kg/d). Blood pressure was measured via carotid artery cannulation. Real-time RT-PCR and Western blotting were performed to assess the mRNA and protein expression, respectively. Myocardium was stained for determination of cardiomyocytes area and fibrosis. Lipid peroxidation levels and the activities of antioxidant enzymes were measured in left ventricular tissue. Results: VitD significantly reduced hypertrophy markers (blood pressure, heart-to-body weight ratio, cardiomyocytes area, fibrosis as well as atrial and brain natriuretic peptides mRNA levels) compared to untreated groups (P < 0.05). VitD also improved the activity of antioxidant enzymes and reduced lipid peroxidation levels in the myocardium (P < 0.05). LVH hearts of untreated animals displayed a significant increase in Rac1 expression compared with the control group (P < 0.05). In contrast, cardiac Rac1, at either mRNAs or protein levels, was markedly lower in LVH animals receiving VitD compared with their untreated counterparts (P < 0.05). Conclusion: Our findings attest that VitD mitigates hallmarks of LVH imparted by pressure overload. Notably, VitD appears to perform its anti-LVH function partly through small GTPase Rac1 suppression. This, in turn, provides a robust incentive to consider VitD before LVH culminates in HF devastating disease.